Chicana Alliance la Universidad de San José - Chicana Alliance::::::::::::::: (2024)
Document describing the challenges and objectives of the Chicana Alliance la Universidad de San José, a SJSU organization dedicated to supporting Chicanas in their personal and collective growth. It highlights the unique struggles faced by Chicanas, including balancing their cultural identity with the demands for security and equality as women.